Risk assessment framework and modeling for underground rock construction project - Sirichat Vonsomtakul. (2011)
This Final Year Project (FYP) Report covers the basic fundamentals of risks and risk management for an underground rock construction project, and development of a cost-benefit risk assessment framework for set-up models based on different scenarios. Despite various uncertainties involved in rock construction, there is evidence indicating that geological risk, which includes uncertainties in rock and construction types play a major role. Thus, in this project, the risk analysis framework will be built on this concept. The cost-benefit assessment will evaluate consequences on the identified risks in terms of construction time and costs. The report will start off with recognizing the increasing needs to develop a systematic risk analysis framework as an integral part of a robust risk management procedure. Then the author will explain about risk nature and risk management stages so as to provide a better understanding of overall risks, followed by the studies of construction types, rock mechanics and rock classifications. Next different risk analysis methodologies will be reviewed and the most suitable method, Monte Carlo Simulation will be selected to perform quantitative analysis on parametric studies with some assumptions according to set-up models and scenarios. The main platform used to carry out a simple Monte Carlo Simulation is Microsoft Excel which is an excellent as well as easy to understand technical tool. In addition, the data used for the simulation process is gathered from the ambiguous numbers from geologist’s consultation which include advancement rates and unit cost (in $1000). The simulation results will be generated as construction time and cost for the project which can be used at the tendering and during the on-going stage of underground construction projects. By assessing all results in given ground profiles, the best possible decisions can be made to manage risks, mitigate their negative consequences, and align with the company’s goals.